2016
DOI: 10.1002/mats.201600073
|View full text |Cite
|
Sign up to set email alerts
|

Spherically Symmetric Solvent is Sufficient to Explain the LCST Mechanism in Polymer Solutions

Abstract: The mechanism of the lower critical solution temperature (LCST) in thermoresponsive polymer solutions has been studied by means of a coarse‐grained single polymer chain simulation and a theoretical approach. The simulation model includes solvent explicitly and thus accounts for solvent interactions and entropy directly. The theoretical model consists of a single chain polymer in an implicit solvent where the effect of solvent is included through the intrapolymer solvophobic potential proposed by Kolomeisky and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 50 publications
(105 reference statements)
1
13
0
Order By: Relevance
“…All the studies were performed on a N = 200 chain in 5000 (N s +N c ) beads of the solvent mixture. In our previous work on a polymer in a pure solvent, 46 we observed a decrease in R g with temperature for as = 1.7, 1.8. Hence, the simulations were performed on three different polymer-solvent interactions; as = ac = 1.7, 1.8, 2.0 at three different temperatures (T = 0.55, 0.65, 0.75).…”
Section: Aa Hh Ss(cc) Ah Hs(hc) As(ac) Csmentioning
confidence: 67%
See 4 more Smart Citations
“…All the studies were performed on a N = 200 chain in 5000 (N s +N c ) beads of the solvent mixture. In our previous work on a polymer in a pure solvent, 46 we observed a decrease in R g with temperature for as = 1.7, 1.8. Hence, the simulations were performed on three different polymer-solvent interactions; as = ac = 1.7, 1.8, 2.0 at three different temperatures (T = 0.55, 0.65, 0.75).…”
Section: Aa Hh Ss(cc) Ah Hs(hc) As(ac) Csmentioning
confidence: 67%
“…The phase transition occurs when x > 1. In our previous study, 46 we showed that the LCST in the case of pure solvent is dependent on the competition between the mean energy difference between the bulk and the bound solvent (U BS − U US ), and the bound solvent…”
Section: B Theoretical Modelmentioning
confidence: 99%
See 3 more Smart Citations